Biomechanical evaluation of internal fixation implants for femoral neck fractures: A comparative finite element analysis. (November 2020) - Zeng, Wei; Liu, Yin; Hou, Xue
Highlights: Twenty FE models were developed to compare biomechanical performance of internal fixation implants for Pauwels type III femoral neck fractures: DHS, CSs, PFNA, DHS+MBP and CSs+MBP. Physiological realistic loadings were considered to evaluate strain in bone and stress in devices during walking and stair climbing conditions. No significant difference was observed regarding the risks of bone fracture and device failure between DHS and CSs. PFNA showed better biomechanical behaviors than DHS and CSs under both static and dynamic loadings. The medial buttress plate (MBP) can provide an additional load path to dissipate stress in the DHS lag screw or in the cannulated screws. Abstract: Background and Objective: It remains controversial regarding the optimal type of fixation implant for the treatment of femoral neck fractures (FNFs). Biomechanical rational for implant choices can benefit from the integration of finite element analysis (FEA) in device evaluation and design improvement. In this study, we aim to evaluate biomechanical performance of several internal fixation implants for Pauwels type III FNFs under physiological loading conditions using FEA, as well as to assess the biomechanical contribution of medial buttress plate (MBP) augmentation. Methods: Several fixation styles for FNFs have been analyzed numerically by the finite element method. Five groups of models were developed with different FNFs fixation implants, including dynamic hip screw (DHS), cannulated screws (CSs), proximal femoral nail antirotation (PFNA), DHS with MBP augmentation (DHS+MBP), and CSs with MBP (CSs+MBP). For each group, four FE models were established to evaluate strain in bone and stress in devices during walking and stair climbing conditions, which simulated the hip contact force using static and dynamic loadings respectively. Results: No notable differences were observed in peak strain within implanted bone and maximum stress values of the device between DHS and CSs. The implanted femur with PFNA was in a lower state of bone strain and implant stress. Although the buttress plate did not decrease peak bone strain, it alleviated stress concentration on device, especially for CSs under dynamic loadings. Conclusions: Compared to the other fixation styles, the PFNA showed biomechanical advantages of decreasing risk of implant failure and bone yielding. The MBP augmentation provided an additional load path to bridge fracture fragments, which reduced failure risk of DHS and CSs, especially during dynamic loading scenarios. Although further studies are needed for patients with other types of FNFs, our findings may provide valuable references for device design optimization in terms of complex physiological loadings, as well as for clinical decision making in surgical treatment of FNFs.